The association between information and communication technologies, loneliness and social connectedness: A scoping review - Petersen, Berkley; Khalili-Mahani, Najmeh; Murphy, Caitlin; Sawchuk, Kim; Phillips, Natalie; Li, Karen Z. H.; Hebblethwaite, Shannon (Frontiers in Psychology, 2023)
Older adults are at a higher risk of loneliness, compared to other demographics. The use of Internet Communication and Technologies (ICTs) among older adults is steadily increasing and given ICTs provide a means of enhancing social connectedness suggests they may have positive effects on reducing loneliness. Therefore, the aim of this scoping review was to examine the research that explores how ICTs may be implicated in mitigating loneliness and increasing social connectedness among older adults. After the examination of 54 articles, we identified 3 major themes within the literature: 1) ICTs were associated with a reduction in loneliness and increase in wellbeing. 2) ICTs promoted social connectedness by facilitating conversations. 3) Factors such as training, self-efficacy, self-esteem, autonomy, and the design/features, or affordances, of ICTs impacts the associations between ICT use and wellbeing. The heterogeneity of methodologies, statistical reporting, the small sample sizes of interventional and observational studies, and the diversity of the experimental contexts underline the challenges of quantitative research in this field and highlights the necessity of tailoring ICT interventions to the needs and contexts of the older users.